Biallelic loss‐of‐function HACD1 variants are a bona fide cause of congenital myopathy. Issue 4 (16th January 2021) - Abbasi‐Moheb, Lia; Westenberger, Ana; Alotaibi, Maha; Alghamdi, Malak Ali; Hertecant, Jozef L.; Ariamand, Amir; Beetz, Christian; Rolfs, Arndt; Bertoli‐Avella, Aida M.; Bauer, Peter
Abstract: Congenital myopathies include a wide range of genetically determined disorders characterized by muscle weakness that usually manifest shortly after birth. To date, two different homozygous loss‐of‐function variants in the HACD1 gene have been reported to cause congenital myopathy. We identified three patients manifesting with neonatal‐onset generalized muscle weakness and motor delay that carried three novel homozygous likely pathogenic HACD1 variants. The two of these changes (c.373_375+2delGAGGT and c.785‐1G>T) were predicted to introduce splice site alterations, while one is a nonsense change (c.458G>A). The clinical presentation of our and the previously reported patients was comparable, including the temporally progressive improvement that seems to be characteristic of HACD1 ‐related myopathy. Our findings conclusively confirm the implication of HACD1 in the pathogenesis of congenital myopathies, corroborate the main phenotypic features, and further define the genotypic spectrum of this genetic form of myopathy. Importantly, the genetic diagnosis of HACD1 ‐related myopathy bears impactful prognostic value. Abstract :